Mangkuk Tingkat System - Nurfarahin Zafir,; Mazida Ahmad,; Norliza Katuk, (Multidisciplinary Applied Research and Innovation, 2021)
An organized menu that provides a list of available dishes is essential, especially food vendors. A paperless menu can easily be created using a Mangkuk Tingkat System, which will facilitate food vendors in organizing the list of food and beverages effectively and efficiently. In addition, the system helps to overcome the problems of missing pages and misplaced menus. Therefore, using the Mangkuk Tingkat System, the creation and searching of a dish or meal in the menu will be much simpler. To bridge this gap, this study aims to design and develop a mobile application to create and manage food menus using smartphones. The development of the mobile system used the Waterfall methodology. The functional requirements were gathered using questionnaire. The construction of the prototype began once the data were analysed. The results obtained from the prototype evaluation suggested that the Mangkuk Tingkat System is useful and easy to use. The respondents were also satisfied and gave beneficial feedbacks on the system. The study contributes towards an understanding of mobile system requirements and use interface in managing the list of menus. This can prove and give confidence to other researchers to continue and further develop such applications in the future.